Rare manifestations of cryoglobulinemic vasculitis: a case report - Leleux, Charlotte; Zerbib, Yoann; Pommerolle, Pierre; Da Rocha, Audrey; Serpier, Marine; Caillard, Pauline (Frontiers in Immunology, 2023)
Introduction Cryoglobulinemic vasculitis is a type of small vessel vasculitis diseases that can cause dysfunction in multiple organs. It is characterized by general symptoms, often accompanied by nonspecific cutaneous, articular, neurological, and renal manifestations. Diagnosing cryoglobulinemia through biological testing can be time-consuming and sometimes yields negative results, making diagnosis challenging. There are also other potentially life-threatening complications that can significantly impact prognosis and delay urgent treatment, including digestive manifestations and heart failure. Case presentation We report the case of a 60-year-old male patient with a medical history of rheumatoid arthritis. He was admitted to the Nephrology Department for investigation of necrotic vascular purpura, acute kidney injury, and pancytopenia. Laboratory tests revealed consumption of the C3 and C4 complement fractions and the presence of mixed-type III cryoglobulinemia. Despite the initiation of the treatment, the patient rapidly developed multiple severe organ failures, including renal, cardiac, respiratory, and finally digestive complications. Acute colic ischemia led to emergency surgery and the patient was transferred to the Intensive Care Unit. Despite surgical intervention and hemodynamic support, the patient experienced multi-visceral organ failure and died two hours after admission. Discussion Mixed cryoglobulinemia vasculitis may result in rare cases of acute and life-threatening organ damage, such as cardiac or respiratory failure with pulmonary hemorrhage, gastrointestinal ischemia, and neurological disorders. These severe manifestations are associated with a poor prognosis and it is crucial to promptly initiate an aggressive therapeutic strategy.